Preparation and physicochemical quality control of elderflower raw material (Sambucus nigra L.) (Research, Society and Development, 2022)
The elderberry flowers (Sambucus nigra) can be used in the treatment of cold and flu symptoms. To ensure the quality of the raw material it is necessary to have quality control tests to establish standards in order to promote the safety and efficacy of the final product. The present study aimed to determine the adequacy of drying conditions to optimize the quality of the plant material for the preparation of elderberry tea. The methodology applied in the work was based on the physical-chemical quality control tests of the Brazilian Pharmacopoeia, performing the sample collection and drying of the flowers, as well as visual examination and macroscopic inspection, purity tests, and determination of polyphenol content. The plant drug sample (flowers) dried at 40ºC for 72h was analyzed and obtained values compatible with the pharmacopoeia recommendations for moisture content (8.7%) and total ash (6.97%); the infusion presented an average of 0.46% of dry residue and the average pH value was 5.12, the average value of total polyphenols was 0.15%. Through the parameters obtained in this study it is possible to create measures to ensure the use of the vegetable drug with quality, provided that there is total supervision of the processing, from planting to the product.